Feeling Pain/Making Kin in the Brooklyn Noise Music Scene - Farrow, David (Current Musicology, 2020)
In the Brooklyn Do-It-Yourself noise music scene, the distinction between subculture and family blurs. Drawing from ethnographic research at Brooklyn Do-It-Yourself venues conducted between February 2018-December 2019, this article explores the formation of queer kinship as material and emotional support for queer life within this scene. Pain in mosh pits, grief over the death of a musician, and love for each other organize obligations, dependencies, and concern amongst strangers. At the same time, real estate developers exploit DIY artistic labor to facilitate gentrification. Queer kinship networks within DIY communities must stand in solidarity with their neighbors, but DIY venues and scenes must first end their complicity in gentrification.